The State and Economy in Postpandemia. Old and New Theoretical and Practical Questions - Frąckowiak, Waldemar (DEMO, 2020)
Where will the world go to, what roles and relations will be formed between the state and economy in face of redefined globalization, all-embracing Internet, risk and uncertainty growth and periodical economic, ecologic and epidemic turbulances ? Will solely modified version of existing market mechanism emerge based on an old paradigm : "more, faster, better" ? Or will changes be so deep that the social and economic world to follow a new paradigm ? Answers to those questions are issues of greatest intelectual challenge in this paper. In order to find answer : "What state in what economy ?" three subsequent problems are considered : -- identification of main conclusions of economic thought on the role of state and economy within last 2500 years, -- capacity of leading socio-economic doctrines functionning in the European and American practice to deal effectively with upcoming challenges in particular social expectations, -- new challenges facing states, economies and societies from the future world economic development point of view (the Polish case is included). From the methodological perspective postulates and conclusions of the paper are based on holistic approach merging main streams of theory of economy with institutionalism, organization and management theory, sociology and political science. Based on research made the general conclusion was drawn the revision of economic philosophy, role and relations of state and economy is necessary. Economy based on existing paradigm is dominated by primacy of economic and quantitative goals while social and qualitative goals are undervalued. These goals should be equivalent, interdependent, cosignificant and co-contributing to an expected well-being and quality of life. Additionally balance, harmony and adequacy of economic, social and institutional capital are required. Apart from stimulating an economic growth this is a main task of the state. There is also a need to have an economy based on freedom, equality and competition and these values must be protected by state. In turn the state is needed that is above market if it fails and when it realizes important social goals aiming at quality of life growth. The state which is out of class organization with neutral philosophy of life and at once organization of consented social coercion only to a degree to get enough capacity to achieve national, social and economic goals.(original abstract)
Keywords: State; Economy; Management paradigms; Economic theory